Age of Shōjo : the emergence, evolution, and power of Japanese girls' magazine fiction - Dollase, Hiromi Tsuchiya, 1968- (State University of New York Press, 2019)
"Hiromi Tsuchiya Dollase examines the role that magazines have played in the creation and development of the concept of shōjo, the modern cultural identity of adolescent Japanese girls. Cloaked in the pages of girls' magazines, writers could effectively express their desires for freedom from and resistance against oppressive cultural conventions. Shōjo characters' "immature" qualities and social marginality gave authors the power to express their thoughts without worrying about the reaction of authorities. Age of Shōjo details the transformation of Japanese girls' fiction from the 1900s to the 1980s, including the adaptation of Western stories such as Louis May Alcott's Little Women in the Meiji period; the emergence of young female writers in the 1910s and the flourishing girls' fiction era of the 1920s and 1930s; the changes wrought by state interference during the war; and a new era of empowered post-war fiction. The book highlights seminal author Yoshiya Nobuko's dreamy fantasies and Kitagawa Chiyo's social realism, Morita Tama's autobiographical feminism, the contributions of Nobel Prize winning author Kawabata Yasunari, and the humorous modern fiction of Himuro Saeko and Tanabe Seiko. These authors address social topics such as education, same-sex love, feminism, and socialism using girls' perspectives. The age of shōjo, which began at the turn of the twentieth century, continues to nurture new generations of writers and entice audiences beyond age, gender, and nationality"--